2022
DOI: 10.1055/s-0042-1744495
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Obesity and Reproductive Function in Adolescents

Abstract: Obesity is increasing worldwide, including in pediatrics. Adequate nutrition is required for initiation of menses, and there is a clear secular trend toward earlier pubertal onset and menarche in females in countries around the globe. Similar findings of earlier pubertal start are suggested in males. However, as individuals and populations have crossed into over-nutritional states including overweight and obesity, the effect of excess weight on disrupting reproductive function has become apparent. Hypothalamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 181 publications
(356 reference statements)
0
7
0
Order By: Relevance
“…One possible hypothesis for such a result is that the girls investigated have not yet reached the age of menarche, since we are evaluating the age group of 7 to 10 years and the mean age at menarche in our sample was 12.3 years in 2007 and 2012/2013 and 11.9 years in 2018/2019 (Matsuo et al., 2022). Thus, probably they had not experienced the impact of body fat accumulation that is expected after the menarche (Elliott et al., 2022). Another explanation might be that girls tend to consume more healthy foods such as fruits and vegetables than boys (Rasmussen et al., 2006), and therefore, they may have an adequate bodyweight compared to boys.…”
Section: Discussionmentioning
confidence: 99%
“…One possible hypothesis for such a result is that the girls investigated have not yet reached the age of menarche, since we are evaluating the age group of 7 to 10 years and the mean age at menarche in our sample was 12.3 years in 2007 and 2012/2013 and 11.9 years in 2018/2019 (Matsuo et al., 2022). Thus, probably they had not experienced the impact of body fat accumulation that is expected after the menarche (Elliott et al., 2022). Another explanation might be that girls tend to consume more healthy foods such as fruits and vegetables than boys (Rasmussen et al., 2006), and therefore, they may have an adequate bodyweight compared to boys.…”
Section: Discussionmentioning
confidence: 99%
“…Despite different observations on the onset of puberty in obese adolescents, some studies present that, apart from an advanced bone age potentially decreasing final height, persistent obesity may suppress the HPG axis thereafter [104,124].…”
Section: Functional Hypogonadotropic Hypogonadism In Obese Adolescentsmentioning
confidence: 98%
“…Many research groups focus on the mechanisms underlying the influence of obesity on puberty [104][105][106][107][108][109][110][111][112]. The activation of the HPG axis is triggered by pulsatile GnRH secretion influenced by the activity of KnDY neurons (KNDY: kisspeptin, neurokinin B, and dynorphin) [106][107][108].…”
Section: Functional Hypogonadotropic Hypogonadism In Obese Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased body mass index (BMI) is associated with various diseases, including pulmonary, gastrointestinal, liver, cardiovascular, diabetes mellitus and insulin resistance, metabolic, and renal diseases [39][40][41][42][43]. Asgary et al found a significant reduction in the BMI among 20 patients receiving 500 mg/day HSE powder where a BMI at baseline and at four weeks was 27.51 vs 27.27 kg/m 2 in the experimental group, yet no statistical significance noted among the placebo and experimental group [23].…”
Section: Metabolic Health Blood Glucose and Lipid Profilementioning
confidence: 99%